Identification, characterization, and evolution of a primate β-defensin gene cluster - Radhakrishnan, Y (2005)
Defensins are members of a large diverse family of cationic antimicrobial peptides that share a signature pattern consisting of six conserved cysteine residues. Defensins have a wide variety of functions and their disruption has been implicated in various human diseases. Here we report the characterization of DEFB119–DEFB123, five genes in the human β-defensin cluster locus on chromosome 20q11.1. The genomic structures of DEFB121 and DEFB122 were determined in silico. Sequences of the five macaque orthologs were obtained and expression patterns of the genes were analyzed in humans and macaque by semiquantitative reverse transcription polymerase chain reaction. Expression was restricted to the male reproductive tract. The genes in this cluster are differentially regulated by androgens. Evolutionary analyses suggest that this cluster originated by a series of duplication events and by positive selection. The evolutionary forces driving the proliferation and diversification of these defensins may be related to reproductive specialization and/or the host–parasite coevolutionary process.